Actions regarding cooperation within the national territory of Mexico within the framework of the Comprehensive Development Plan and the Migration Policy - Sandoval Salas, Gloria (Revista Española de Desarrollo y Cooperación, 2021)
This article analyzes the intensification of the flows of people who intend to settle in the United States of North America, generating problems and various challenges for the Mexican State in their wake. In this sense, the Government of Mexico has designed a development plan that combines efforts in humanitarian and legal assistance and support for applicants and refugees. Through the Mexican Agency for International Development Cooperation, this integrated plan is implemented in turn in the planning of the Economic Commission for Latin America and the Caribbean (ECLAC) and aimed at improving the migratory stations and shelters that operate in the Mexican territory.
Keywords: Migration; Immigration stations; Shelters; Fundamental rights